2021
DOI: 10.1186/s10397-021-01096-5
|View full text |Cite
|
Sign up to set email alerts
|

Medical and surgical interventions to improve the quality of life for endometriosis patients: a systematic review

Abstract: Endometriosis impairs the quality of life (QoL) of many women, including their social relationships, daily activity, productivity at work, and family planning. The aim of this review was to determine the instruments used to examine QoL in previous clinical studies of endometriosis and to evaluate the effect of medical and surgical interventions for endometriosis on QoL. We conducted a systematic search and review of studies published between January 2010 and December 2020 using MEDLINE. Search terms included “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 91 publications
(164 reference statements)
0
29
0
1
Order By: Relevance
“…All these results indicated that DIE surgery could effectively improve pain symptoms. D’Alterio et al [ 37 ] demonstrated that many medical and surgical treatments could demonstrate benefits in pain control and quality-of-life improvement. Overall, the surgical approach for severe DIE may be more effective and decisive.…”
Section: Discussionmentioning
confidence: 99%
“…All these results indicated that DIE surgery could effectively improve pain symptoms. D’Alterio et al [ 37 ] demonstrated that many medical and surgical treatments could demonstrate benefits in pain control and quality-of-life improvement. Overall, the surgical approach for severe DIE may be more effective and decisive.…”
Section: Discussionmentioning
confidence: 99%
“…This study found an improvement in all physical and mental aspects of the QoL. The Endometriosis Health Profile-30 (EHP-30) questionnaire is more specific and should be adopted in cases where the diagnosis of endometriosis is ultrasound or surgically confirmed [ 16 ]. The SF-36 questionnaire was chosen to use in the current investigation because the study was based on the pain symptoms suggestive of endometriosis diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Those with endometriosis report a significant economic burden [ 8 ], issues at work [ 9 ] and in education [ 7 ], poor mental health [ 10 , 11 ] and the breakdown of sexual relationships [ 7 ]. All of this contributes to the reduced quality of life [ 12 ] reported by those with the disease.…”
Section: Introductionmentioning
confidence: 99%